The nuclear receptor constitutive active/androstane receptor (CAR) arrests DNA-damaged human hepatocellular carcinoma Huh7 cells at the G2/M phase - Kamino, Hiroki (2011)
Here we have demonstrated that xenobiotic activation of the nuclear receptor CAR (NR1I3) can result in arresting DNA-damaged human hepatocellular carcinoma Huh7 cells at the G2/M phase. Huh7 cells over-expressing CAR were either treated with DMSO, the CAR activator TCPOBOP, or repressor androstenol; these treatments were then followed by adriamycin treatment to damage DNA. FACS analysis revealed that CAR-activation by TCPOBOP increased the rate of arrested Huh7 cells at the G2/M phase (4N DNA content) after DNA damage by adriamycin. This increase correlated with the increase of cell viability in TCPOBOP-treated Huh7 cells, as determined by MTT assays. Real-time PCR analysis determined that, as regulated by CAR, the growth arrest and DNA damage-inducible γ (GADD45γ) and Cyclin G2 genes increased and decreased, respectively, as TCPOBOP increased the number of Huh7 cells arrested at the G2/M phase. Thus, the results suggest that CAR regulates cell cycle, increasing G2/M arrest and delaying the death of DNA-damaged cells.